Impact of increased anthropogenic Amazon wildfires on Antarctic Sea ice melt via albedo reduction - Sudip Chakraborty; Maloy Kumar Devnath; Atefeh Jabeli; Chhaya Kulkarni; Gehan Boteju; Jianwu Wang; Vandana P. Janeja (Environmental Data Science)
This study shows the impact of black carbon (BC) aerosol atmospheric rivers (AAR) on the Antarctic Sea ice retreat. We detect that a higher number of BC AARs arrived in the Antarctic region due to increased anthropogenic wildfire activities in 2019 in the Amazon compared to 2018. Our analyses suggest that the BC AARs led to a reduction in the sea ice albedo, increased the amount of sunlight absorbed at the surface, and a significant reduction of sea ice over the Weddell, Ross Sea (Ross), and Indian Ocean (IO) regions in 2019. The Weddell region experienced the largest amount of sea ice retreat (